CHAPTER FOURTEEN ELEMENTAL PROXIES FOR PALAEOCLIMATIC AND PALAEOCEANOGRAPHIC VARIABILITY IN MARINE SEDIMENTS: INTERPRETATION AND APPLICATION - Calvert S.E.; Pedersen T.F. (My University, 2007)
This chapter discusses the elemental proxies for palaeoclimatic and palaeoceanographic variability in marine sediments. Physical and biological processes during deposition coupled with post-depositional chemical reactions yield a complex component mixture that can provide significant palaeoceanographic and palaeoclimatic information to complement and strengthen interpretations derived from the study of microfossils and the isotopic compositions of sedimentary components. The chapter reviews the application of sedimentary geochemistry to the reconstruction of climatic and oceanographic changes over the Cenozoic, with emphasis on the Late Pleistocene. Records from both pelagic regimes and ocean margin provinces are used to show how information on both ocean conditions and terrestrial climates can be assembled from the major, minor and trace element composition of sea-floor deposits. The chapter provides background sedimentary information, and describes some common data manipulation techniques that are used to construct and study palaeoclimatic and palaeoceanographic records in marine sediments.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен